Reliability and Lifetime Assessment of Glider Wing’s Composite Spar through Accelerated Fatigue Life Testing - Zaharia, Sebastian Marian; Pop, Mihai Alin; Udroiu, Răzvan (MDPI AG, 2020)
The evaluation of the reliability and the lifetime of aerospace components has become an important segment of the design stage. The aeronautical components are subjected to complex, rigorous tests and have a long test life. The main goal in the field of aviation is to have components with high reliability and quality and to meet the mandatory requirements and regulations. The spars are stiffening components positioned along the wing and which take up most of the load and are tested for fatigue over a long period of time. The spar which was analysed in this study has a sandwich structure with GFRP (glass fiber reinforced plastic) skin and foam core. In this paper, the performances in the static and dynamic conditions of the GFRP-foam sandwich structures cut out of the composite spar of a glider were analysed. Additionally, using accelerated techniques based on the three-point fatigue bending test, the main reliability indicators of the GFRP-foam sandwich structures were determined. Using the statistical processing of the experimental data and the Inverse Power Law–Weibull acceleration model, the mean number of cycles to failure, in normal testing conditions of the GFRP-foam specimens was determined, with a value of 102,814. Using the accelerated testing techniques of the GFRP-foam sandwich structures an important decrease of the test time (8.43 times) was obtained.
Keywords: composite spar; accelerated fatigue life testing; reliability; lifetime; glider